Digital Support Education on Risky Adolescent Reproductive Health Behaviors: A Systematic Review - Rumdari Rumdari; Setyowati Setyowati; Tri Budiati; Imami Nur Rachmawati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Adolescents are a group vulnerable to reproductive health issues. One contributing factor is a lack of literacy and limited access to sexual and reproductive health services. Educational interventions supported by digital technology, such as mobile applications, websites, and social media, aim to provide information related to sexual and reproductive health. These interventions are expected to reduce risky behaviors, including preventing sexually transmitted infections, unwanted pregnancies, and making appropriate reproductive health decisions. However, the effectiveness of digital-supported educational interventions remains variable. Objective: examined the effectiveness of health education using digital support from various journal articles. Method: systematic review approach was used to analyze and evaluate several research results through literature searches with Proquest, Wiley, Science Direct and Spinger Link databases with experimental and RCT research types. Results: The results of a review of thirteen articles can be concluded that interventions with digital support can significantly ( <0.05) increase adolescents' knowledge about reproductive health, improve attitudes towards preventing adolescent health risk behaviors, improve behavior in maintaining reproductive health disease prevention, increase self-efficacy and reduce the incidence of physical violence and sexual violence. Recommendations: It is recommended that interventions involve both adolescents and their parents, as parental roles are crucial in providing support to adolescents.